2009
DOI: 10.1007/s11427-009-0136-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic phenotype and identification of “heart blood stasis obstruction pattern” and “qi and yin deficiency pattern” of myocardial ischemia rat models

Abstract: The traditional Chinese medicine concepts of "Xinxueyuzuzheng (heart blood stasis obstruction pattern)" and "Qiyinliangxuzheng (qi and yin deficiency pattern)" for myocardial ischemia rat models were constructed in the present study. Endogenous metabolites in rat plasma were analyzed using the GC/TOF-MS-based metabonomic method. Significant metabolic differences were observed between the control and two model groups, and the three groups were distinguished clearly by pattern recognition. Compared with those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The TCM concepts of "Xinxueyuzuzheng (heart blood stasis obstruction pattern)" and "Qiyinliangxuzheng (qi and yin deficiency pattern)" for myocardial ischemia rat models were constructed by Yan et al Endogenous metabolites in rat plasma were identified, such as valine, serine, threonine, ornithine, hydroxyproline, lysine, 2-hydroxybutanoic acid, 3-hydroxybutanoic acid, galactofuranose, and inositol. These compounds were indicated as the potential biomarkers, suggesting that the two above-mentioned patterns are involved in dysfunction, oxidative stress, energy metabolism, and amino acid metabolism [88]. Chen et al described the metabolomic study of a biochemical modification in vivo induced by a high dose of hydrocortisone, which led to a unique pathologic condition similar to the "kidney deficiency syndrome", an early stage of obesity and diabetes in TCM [89].…”
Section: Metabolomics In Chinese Medicine Syndromesmentioning
confidence: 99%
“…The TCM concepts of "Xinxueyuzuzheng (heart blood stasis obstruction pattern)" and "Qiyinliangxuzheng (qi and yin deficiency pattern)" for myocardial ischemia rat models were constructed by Yan et al Endogenous metabolites in rat plasma were identified, such as valine, serine, threonine, ornithine, hydroxyproline, lysine, 2-hydroxybutanoic acid, 3-hydroxybutanoic acid, galactofuranose, and inositol. These compounds were indicated as the potential biomarkers, suggesting that the two above-mentioned patterns are involved in dysfunction, oxidative stress, energy metabolism, and amino acid metabolism [88]. Chen et al described the metabolomic study of a biochemical modification in vivo induced by a high dose of hydrocortisone, which led to a unique pathologic condition similar to the "kidney deficiency syndrome", an early stage of obesity and diabetes in TCM [89].…”
Section: Metabolomics In Chinese Medicine Syndromesmentioning
confidence: 99%
“…In addition to haemorheological disorders, energy metabolism also plays pivotal roles in coronary heart diseases with blood stasis syndrome [37]. Both Na + -K + ATPase and Ca 2+ ATPase are ubiquitous membrane-associated proteins and can maintain the electrochemical gradient inside and outside the myocytes using the energy of ATP hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen related pathways and four main pathological processes including oxidative injury, energy metabolism dysfunction, amino acid metabolism dysfunction and inflammation are involved in myocardial infarction development. Sheng‐mai injection could normalize the level of plasma endothelin‐1, the index related to cardiovascular diseases and sleep disorders, which verified the results of metabolomics (Yan et al ., ). The regulated metabolites and related metabolic pathways were analyzed, and it was supposed that the effects of Sheng‐mai injection involved in the alternation of energy metabolism, lipid metabolism, amino acids metabolism and so on.…”
Section: Metabolomics In Application Of Tcmmentioning
confidence: 97%